Altare contra altare. Dysputa o kształcie ołtarza i o jego wystroju w epoce nowożytnej - Krasny, Piotr (TECHNE. Seria Nowa, 2018)
Divisions of Western Christianity, initiated in the early 16th century and deepened in the following 200 years, led, among other things, to the embroilment between various Christian denominations regarding the issue of the symbolism of the altar, its functions, shape and location within a church. For Catholics, the altar has primarily remained the place to celebrate the Holy Sacrament, aimed at reiterating the crucifixion of Jesus and, in consequence, offering God’s mercy for those participating in the liturgy and for the whole Church. Martin Luther (1483-1546) rejected this concept of the Eucharist, claiming that – according to the Bible – it was not a sacrifice, but a commemoration of the Lord’s Supper. Under his influence, Martin Bucer (1491-1551), John Calvin (1509-1564) and numerous other reformers recommended substituting mediaeval stone altars with wooden tables, which, as they believed, should accordingly be called Lord’s Tables. The most heated disputes on the issues of the symbolism and the shape of altars were held in the Church of England (Anglicanism). The faction known as the Puritans demanded that reformed solutions be implemented, while another group, described as ‘Ritualists’ opted for the preservation of the Catholic tradition. In the mid-17th century, the former option – justifiably grounded in the treatise by John Williams (1582-1650) – yielded to the latter, which was propagated by John Pocklington (died 1642) and inWilliam Laud’s preaching (1573-1645). The dissimilar perception of the symbolism of the altar, which divided Catholics and Protestants, translated into their attitudes towards the act of its consecration. Catholics believed that it had to be ‘predisposed’ to perform the Lord’s Supper there, since this act – due to its sacramental nature –is significantly more momentous than the ‘papists’ superstitious ceremony’. Medieval theologists preached that the altar symbolises Christ, and the temple building represents the Church that gathers around Him. This symbolism, however, was obliterated in the Roman Church, where in the 6th century numerous side altars began to be erected. This practice was also maintained after the Council of Trent (1545-1563), even if Charles Borromeo (1538-1584) instructed that the central altar, where the most solemn celebrations for crowds of worshippers were held, ought to be noticeably more sumptuous when compared to side altars, which were primarily used for the purpose of private masses. At the same time, Lutherans, who emphasised the community-based nature of the Lord’s Supper, opted for the preservation of a single altar in a church – a postulate avidly advocated by Peder Palladius(1503-1560) in the 1540’s. A similar rule was propagated by writers from other reformative communities. Nevertheless, there was a substantial clash of opinions regarding the location of the altar and the Lord’s Table among Protestants. Lutherans and Anglican Ritualists believed, just like Catholics, that the worship of the Elements of the Eucharist required part of the altar to be separated, by placing it at the eastern wall of the church, and most advantageously in an isolated section of the presbytery. Calvinists and Anglican Puritans claimed that the concept of the Eucharist as vinculum caritatis, which they had applied, implied that the Lord’s Table ought to be placed in the nave, in the middle of the worshipping community. The opinion shared by the majority of writers from various religious backgrounds was that nothing else should be placed on the altar since during the Eucharist it houses its Holy Elements. Catholics did not consider reredoses to be an integral part of altars, and therefore, when describing the places for performing the Eucharist, they often chose not to mention them at all, just like Borromeo. As late as at the end of the 16th century, the necessity of an appropriate selection of themesfor the paintings within reredoses began to be emphasised, in order for these art works to be a suitable ‘commentary’ to the mass liturgy. This necessity was also recognised by Lutherans, who claimed that the altar was, among other things, ‘a testimony of faith’, and thus, it was of crucial importance to determine an appropriate iconographic programme for its reredos, with a particular focus on the Last Supper. A weighty innovation, introduced by Catholics, was placing the tabernacle on the high altar, as advised, for instance, by Gian Matteo Giberti (1495-1543), Borromeo and Jakob Muller (died 1591). Other Catholic writers, however, believed that this solution triggered a semantic tension between the worship of the Eucharistic Christ, stored in the tabernacle, and the Christ who appears on the altar stone when the Mass is being said. Thus, Jean Duvergier de Hauranne (1581-1643) suggested returning to the medieval practice of suspending a pyx on an extension arm over the altar and lowering it onto the altar stone during Holy Communion. Although the dispute on the altar in the Early Modern Period proved to benefactors, architects, sculptors and painters what the fundamental problems were related to its adjustment to the needs of the liturgy, it also left them a substantial amount of freedom in their search for artistic solutions to cope with these issues.